Characterization and Corrosion Behavior of Multilayer [TiAlN]n Growth on AISI 316LVM Steel - Mejia, A.; Roa-Rodríguez, G.; Aperador, W. (ELSEVIER, 2014)
In this article was characterized and evaluated the corrosion behavior of [TiAlN/]n multilayer coatings with 1, 16 and 32 bilayer periods deposited by the magnetron Sputtering PVD technique on stainless steel AISI 316 LVM. The electrochemical behavior that emulated the corporal environment was evaluated by electrochemical impedance spectroscopy using as electrolyte Hank’s solution. After the degradation test, the characterization was performed by scanning electron microscopy (SEM) and the corrosion products were evaluated using X ray diffraction. It was found a remarkable increase of the corrosion resistance with the deposition of multilayer coatings on substrates, evidencing the effect of increase the bilayers in the decrease of the degradation when increasing the polarization resistance of the multilayer coatings, corroborating the good performance of the bilayers period variation.

En este artículo se caracterizó y evaluó el comportamiento a la corrosión de recubrimientos multicapa [TiAlN/]n. con 1, 16 y 32 períodos bicapa depositados mediante la técnica de magnetrón Sputtering PVD sobre acero inoxidable acero AISI 316 LVM. El comportamiento electroquímico que emulaba el ambiente corporal fue evaluado mediante espectroscopía de impedancia electroquímica utilizando como electrolito la solución de Hank. Después del prueba de degradación, la caracterización se realizó mediante microscopía electrónica de barrido (SEM) y la Los productos de corrosión se evaluaron mediante difracción de rayos X. Se encontró un aumento notable de la resistencia a la corrosión con la deposición de recubrimientos multicapa sobre sustratos, evidenciando el efecto de aumentar las bicapas en la disminución de la degradación al aumentar la resistencia a la polarización de los recubrimientos multicapa, corroborando el buen comportamiento de la variación del período de las bicapas.
Keywords: Steel; Acero; Electrochemistry; Electroquímica; Biocompatibility; Biocompatibilidad; Biomaterials; Biomateriales; Corrosion; Multilayers; Multicapas; Characterization; Caracterización; Bode Diagram; Diagrama de Bode